Dr. Gundry's diet evolution : turn off the genes that are killing you-and your waistline-and drop the weight for good - Gundry, Steven R. (Three Rivers Press, 2008)
Does losing weight and staying healthy feel like a battle? Well, it's really a war. Your enemies are your own genes, backed by millions of years of evolution, and the only way to win is to outsmart them. Renowned surgeon and founder of Gundry MD, Dr. Steven Gundry's revolutionary book shares the health secrets other doctors won't tell you.